PENGARUH BUDAYA SEKOLAH TERHADAP PEMBENTUKAN KARAKTER SISWA SMA - Muhamat Zajuli Yusuf; Didit Darmawan (STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
School culture is a crucial factor in shaping the character of high school students, as it serves as a social environment that continuously influences students’ attitudes, values, and behavior. This study was conducted to analyze the impact of school culture on the character development of high school students through a literature review approach. A literature review was employed as the method to analyze journals published in 2020 and later that are relevant to the themes of school culture and student character. The findings of the analysis indicate that school culture influences the development of students’ character, particularly in terms of discipline, responsibility, social character, and religious character. The most influential elements of school culture include teachers serving as role models, the consistency of school rules, the instillation of positive values, and a supportive school climate. This meeting underscores that school culture functions not merely as a set of formal rules, but as a system of values internalized through daily practices within the school environment. Consequently, a deliberate and sustained school culture serves as a critical strategy in supporting the success of character education at the high school level.